The atypical presence of the paternal mitochondrial DNA in somatic tissues of male and female individuals of the blue mussel species Mytilus galloprovincialis - Kyriakou, Eleni (BioMed Central, 2010)
BACKGROUND: In animals mtDNA inheritance is maternal except in certain molluscan bivalve species which have a paternally inherited mitochondrial genome (genome M) along with the standard maternal one (genome F). Normally, the paternal genome occurs in the male gonad, but it can be often found, as a minority, in somatic tissues of males and females. This may happen in two ways. One is through "sperm mtDNA leakage" into somatic tissues, a deviation from the normal situation in which the sperm mtDNA vanishes in females or ends up exclusively in the germ line of males. The other is through "egg heteroplasmy", when the egg contains, in small quantities, the paternal genome in addition to maternal genome. FINDINGS: To test the two hypotheses, we compared the sequences of one of the most variable domains of the M molecule in a somatic tissue (foot) and in the sperm of ten male and in the foot of ten female individuals of M. galloprovincialis. Presence of the M genome was rarer in the foot of females than males. The M genome in the sperm and in the foot of males was identical. CONCLUSIONS: Given that the surveyed region differs from individual to individual, the identity of the M genome in the foot and the sperm of males supports strongly the hypothesis that, at least for the tissue examined, the presence of the M genome is due to sperm mtDNA leakage.